ZAKAT PEGAWAI NEGERI SIPIL KEMENTERIAN AGAMA PERSPEKTIF HUKUM ISLAM - Cory Vidiati (Mutawasith: Jurnal Hukum Islam, 2018)
Zakat, infaq and shadaqah are official institutions in Islam that relate to the property of a person or legal entity, worth of worship as well as social charity useful for the welfare of the people. Law No. 38 of 1999 concerning zakat Article 1 explains, zakat is an asset that must be set aside by a Muslim or a body that is owned by Muslims in accordance with religious provisions to be given to those who are entitled. Zakat is imposed on civil servant salaries, including the type of professional zakat. This research was conducted using a juridical analysis method based on a qualitative doctrinal legal approach with the acquisition of secondary primary data through library research which was then analyzed. From the research results found, zakat in language is growing, blessing, holy, clean, and praiseworthy. According to the term is the obligation of Muslims who have reached nishab to issue a portion of their wealth to certain parties. Revenues sourced from civil servants of the Ministry of Religion of Ciamis Regency who have met the threshold of nishab are attempted to provide zakat to the district BAZNAS. The zakat funds are channeled to mistahiq in the form of traditional consumptive, creative consumptive, traditional productive, creative productive, investment in my human resources, investment in business entities, increasing preaching and worship, religious social services, etc. Civil Servant Zakat in the Ministry of Religion of Ciamis Regency is a new formulation of zakat that does not conflict with Islamic law.